Risk Factors of Asthma Among Children Attending Mosul Hospitals - Abdalwahed, Abdalwahed Maher (Journal of medical and pharmaceutical sciences, 2019)
Background: Asthma is a inflammatory condition of the lung airways resulting in episodic airflow obstruction.Symptoms are produced by irritation of small airways and may include bronchial hyper responsiveness, coughing, mainly at night or early morning. The mutable airflow obstruction is often adjustable, either spontaneously or by management .Objective: to find possible etiological risk factors and their links to Children asthma.Methods: This case-control study was conducted in four pediatric teaching hospitals for the period extending from 1st of April to end of November 2018.A total of 300 children > 15years were chosen randomly from the pediatric outpatient clinic, and divided in two group.Group A : one hundred fifty asthmatic patients were labeled as asthmatic .Group B : one hundred fifty children were matched to group A by age, sex, the group B without any history of asthma.Inclusion criteria for Group A were: Diagnosed as asthmatic by consultant pediatrician and should be respond well to anti asthmatic medication.Inclusion criteria for Group B were: Healthy or apparently healthy and without any history of medical problem or chronic diseases.Any child who is not accompanied by his /her mother or relative, and who didn't meet the selection criteria for the A and B groups will be excluded from the study .Results: After adjusting for possible cofounders; the study showed the factors which had significant association with childhood asthma were parent consanguinity 54%(P
Keywords: asthma in children; Mosul hospitals; genetic and environmental factors